Some properties for probabilistic and multinomial (probabilistic) values on cooperative games. (2nd July 2016) - Domènech, Margarita; Giménez, José Miguel; Puente, María Albina
Abstract : We investigate the conditions for the coefficients of probabilistic and multinomial values of cooperative games necessary and/or sufficient in order to satisfy some properties, including marginal contributions, balanced contributions, desirability relation and null player exclusion property. Moreover, a similar analysis is conducted for transfer property of probabilistic power indices on the domain of simple games.